Construction of Academic Discipline Meaning by Students in Campus Rules Practice (Qualitative Study at AMIK Bukittinggi) - Dennis Haruna; Rhafiiqul Azhari Karim; Januar Januar (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to understand how AMIK Bukittinggi students construct the meaning of academic discipline through campus rules and regulations. The issue raised is how discipline is understood, internalized, and applied by students in the context of academic life and the surrounding local culture. This study uses a qualitative approach with a phenomenological design to explore students' subjective experiences through in-depth interviews, participatory observation, and document analysis. The results show that academic discipline is not only understood as a form of compliance with formal rules, but also as an expression of academic responsibility, moral identity, and a mechanism for adapting to the higher education system. Students interpret discipline flexibly and contextually, while Minangkabau cultural values reinforce the meaning of discipline as a form of self-control and personal honor. In conclusion, academic discipline at AMIK Bukittinggi is a dynamic and reflective social construct that develops through interactions between institutional values, culture, and individual experiences, and is an important foundation in shaping students' character and professional ethics.